Novel Power Reduction Technique for ReRAM with Automatic Avoidance Circuit for Wasteful Overwrite - Takaya Handa; Yuhei Yoshimoto; Kazuya Nakayama; Akio Kitagawa (Active and Passive Electronic Components)
Low-power operations can be great advantageous for ReRAM devices. However, wasteful overwriting such as the SET operation to low-resistance state (LRS) device and the RESET operation to high-resistance state (HRS) device causes not only an increase in power but also the degradation of the write cycles due to repeatedly rewriting. Thus, in this paper, we proposed a novel automatic avoidance circuit for dealing with wasteful overwriting that uses a sense amplifier and estimated the energy consumption reduction rate by conducting a circuit simulation. As a result, this circuit helped to reliably avoid the wasteful overwriting operation to reduce about 99% and 97% of wasteful energy using VSRC and CSRC, respectively.